A cationic water-soluble biphen[3]arene: synthesis, host–guest complexation and fabrication of a supra-amphiphile. Issue 81 (15th August 2016) - Zhou, Jiong; Yang, Jie; Zhang, Zhihua; Yu, Guocan
Abstract : The first cationic water-soluble biphen[3]arene was synthesized, which was used to change the aggregation of the amphiphilic guest in water. Abstract : The first cationic water-soluble biphen[3]arene was synthesized and its host–guest complexation with sodium 1-hexanesulfonate was investigated, which was further used to change the aggregation of the amphiphilic guest in water.